Integrating a Mobile‐Based Gaming Application into a Postsecondary Forest Ecology Course. Issue 1 (16th June 2014) - King, Carolyn; Dordel, Julia; Krzic, Maja; Simard, Suzanne W.
Abstract : Increased disengagement of the current generation of postsecondary students (sometimes referred as "net generation") from traditional instruction coupled with on‐going popularity of games and mobile technologies have prompted interest in game‐based learning in education. The objective of this study was to develop and evaluate the viability of a mobile game‐based learning quest, based on the Questogo platform (website and mobile app) in an undergraduate Forest Ecology course offered at the University of British Columbia (UBC), Vancouver. The disturbance ecology (DE) quest was designed as a self‐study activity that supports field‐based laboratory sections of the course. The quest included instructional, location‐based, and question‐ and answer‐type of tasks that tested students' knowledge of forest and disturbance ecology in an outdoor setting. After completing the DE quest, students provided feedback via an online survey. The majority of students found the DE quest to be a useful self‐study tool, with 81% of respondents indicating that they were able to successfully engage with the mobile game‐based learning technology. Sixty‐six percent of the students would like to also see quests incorporated into other courses and 28% would like to have additional quests in the Forest Ecology course. This study provides a framework for incorporating mobile game‐based learning into outdoor learning activities that offer students an engaging self‐study educational experience.